Nambekó-dabadakibá, o lugar onde o facão foi pendurado – o yara chegou - Contato interétnico e reconfigurações territoriais dos Paiter Suruí na Terra Indígena Sete de Setembro, Cacoal/RO - Kelli Carvalho Melo; Adnilson de Almeida Silva (Confins)
This article is a reflection and analysis about the original representations of Paiter Suruí people since the established contact, in 1969, with the surrounding society. Such contact has provided in new ways of apprehension of their territory, as well as the establishment of exchanges, which have engendered impacts, these mark in the Terra Indígena Sete de Setembro (Paiterey Karah) the configuration of how they started to act in their way of life. Our methodological approach refers to the bibliographic review, through the authors (Cassirer, Cunha, Mindlin, Miller, Ribeiro, Sauer, Santos, Lima, Suruí e Almeida Silva, among others), with qualitative and exploratory emphasis with fieldwork (participant research) and interviews in the territory Sete de Setembro. The approach is based on the theoretical principles of representations present in Cassirer's Phenomenology. The results are expressed in the permanence of their original values, at the same time that changing emerges as a strategy to face new challenges in the socio-political-cultural context of put by today's embracing society.